2018
DOI: 10.1002/dc.23990
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound‐guided fine needle aspiration with liquid‐based cytology preparation in the diagnosis of metastatic small‐cell carcinoma in the pancreas

Abstract: Pancreatic metastasis is extremely rare, particularly from small‐cell lung cancer (SCLC). Studies on the role of endoscopic ultrasound‐guided fine needle aspiration (EUS‐FNA) with liquid‐based cytology (LBC) in the diagnosis of metastatic small‐cell carcinoma in the pancreas have been rarely conducted. We report herein a case of pancreatic metastasis from SCLC diagnosed using EUS‐FNA with LBC (ThinPrep). A 71‐year‐old man presented with chief complaints of hemoptysis and jaundice over the past 1 month. Lung & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…PET/CT was also reported to diagnose ovarian metastasis as initial presentation of pancreatic carcinoma ( 11 ). Besides, endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) is safe in diagnosing solid pancreatic lesions ( 12 , 13 ). It was reported that EUS-FNA with liquid-based cytology could diagnosis the metastatic small-cell carcinoma to the pancreas ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PET/CT was also reported to diagnose ovarian metastasis as initial presentation of pancreatic carcinoma ( 11 ). Besides, endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) is safe in diagnosing solid pancreatic lesions ( 12 , 13 ). It was reported that EUS-FNA with liquid-based cytology could diagnosis the metastatic small-cell carcinoma to the pancreas ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) is safe in diagnosing solid pancreatic lesions ( 12 , 13 ). It was reported that EUS-FNA with liquid-based cytology could diagnosis the metastatic small-cell carcinoma to the pancreas ( 13 ). In fact, surgeons and gynecologists tend to only focus on the pancreatic lesion or the ovarian neoplasm respectively, resulting in a missed diagnosis and delayed therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Rossi et al reported that primary pancreatic malignant lymphoma was successfully diagnosed using immunostaining of LBC specimens for EUS-TA ( 36 ). Son et al showed that immunostaining for TTF-1 and CD56 could be used to diagnose metastatic pancreatic cancer using LBC specimens from EUS-TA ( 37 ). Thus, in cases in which immunostaining is difficult because of insufficient tissue samples, a detailed diagnosis can be made by immunostaining LBC specimens.…”
Section: Immunocytochemistry Using Liquid-based Cytology Specimensmentioning
confidence: 99%
“…The smear cytology (SC) has the problem of cell crowding. A new cytological method named ThinPrep (Hologic Inc., Marlborough, MA, USA) cytologic test (TCT) could overcome the deficiency of SC and result in an accurate diagnosis [5] . In the absence of an on-site cytopathologist, TCT offers good diagnostic efficacy in patients with pancreatic mass lesions [6] .…”
Section: Introductionmentioning
confidence: 99%
“…A new cytological method named ThinPrep (Hologic Inc., Marlborough, MA, USA) cytologic test (TCT) could overcome the deficiency of SC and result in an accurate diagnosis. [5] In the absence of an on-site cytopathologist, TCT offers good diagnostic efficacy in patients with pancreatic mass lesions. [6] In our study, only the TCT process was included to avoid the impact of methodological differences.…”
Section: Introductionmentioning
confidence: 99%